New species of Sangiorgioichthys Tintori and Lombardo, 2007 (Neopterygii, Semionotiformes) from the Anisian of Luoping (Yunnan Province, South China) - López-Arbarello, Adriana; Sun, Zuo-Yu; Sferco, Emilia; Tintori, Andrea; Xu, Guang-Hui; Sun, Yuan-Lin; Wu, Fei-Xiang; Jiang, Da-Yong (Zootaxa, 2011)
We report on a new species of the neopterygian genus Sangiorgioichthys Tintori and Lombardo, 2007, from middle Anisian (Pelsonian) deposits in South China (Luoping County, Yunnan Province). Sangiorgioichthys was previously known from a single species, S. aldae, from the late Ladinian of the Monte San Giorgio (Italy and Switzerland). The recognition of the new species helped to improve the diagnosis of the genus, which is mainly characterized by the presence of broad posttemporal and supracleithral bones, one or two suborbital bones occupying a triangular area ventral to the infraorbital bones and lateral to the quadrate, and elongate supramaxilla fitting in a an excavation of the dorsal border of the maxilla. Sangiorgioichthys sui n. sp. differs from the type species in having two pairs of extrascapular bones, the medial pair usually fused to the parietals, maxilla with a complete row of small conical teeth, long supramaxilla, more than half of the length of the maxilla, only two large suborbital bones posterior to the orbit, and flank scales with finely serrated posterior borders. With the discovery of S. sui n. sp., the number of fish genera shared by the Anisian/Ladinian deposits in the Alps and the Anisian deposits in South China increases, including not only the cosmopolitan Birgeria and Saurichthys, but also, among others, the subholosteans Colobodus (so far only in Panxian), Luopingichthys (so far only in Luoping), Peltopleurus, Habroichthys, and the very specialized neopterygians Placopleurus and Marcopoloichthys (only in Luoping). Therefore, although several fish taxa remain to be studied in the Chinese faunas, the so far available evidence indicates close biogeographic relationship between the Middle Triassic marine faunas of the Western Tethys region.